Towards a strong virtue ethics for nursing practice - Armstrong, Alan E. (Nursing philosophy, 2006)
Illness creates a range of negative emotions in patients including anxiety, fear, powerlessness, and vulnerability. There is much debate on the ‘therapeutic’ or ‘helping’ nurse-patient relationship. However, despite the current agenda regarding patient-centred care, the literature concerning the development of good interpersonal responses and the view that a satisfactory nursing ethics should focus on persons and character traits rather than actions, nursing ethics is dominated by the traditional obligation, act-centred theories such as consequentialism and deontology. I critically examine these theories and the role of duty-based notions in both general ethics and nursing practice. Because of well-established flaws, I conclude that obligation-based moral theories are incomplete and inadequate for nursing practice. I examine the work of Hursthouse on virtue ethics’ action guidance and the v-rules. I argue that the moral virtues and a strong (action-guiding) version of virtue ethics provide a plausible and viable alternative for nursing practice. I develop an account of a virtue-based helping relationship and a virtue-based approach to nursing. The latter is characterized by three features: (1) exercising the moral virtues such as compassion; (2) using judgement; and (3) using moral wisdom, understood to include at least moral perception, moral sensitivity, and moral imagination. Merits and problems of the virtue-based approach are examined. I relate the work of MacIntyre to nursing and I conceive nursing as a practice: nurses who exercise the virtues and seek the internal goods help to sustain the practice of nursing and thus prevent the marginalization of the virtues. The strong practice-based version of virtue ethics proposed is context-dependent, particularist, and relational. Several areas for future philosophical inquiry and empirical nursing research are suggested to develop this account yet further.